2008
DOI: 10.1007/s10704-008-9247-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional stress fields near notches and cracks

Abstract: Structures with notches have a tendency to develop critical crack growth because of the stress concentration. The strength of the structures with stress gradient usually shows strong three-dimensional (3D) effects even under in-plane loading. The commonly twodimensional (2D) models for fracture assessments of bodies with notches and cracks may lead to inaccurate predictions when in-plane loading is applied to certain 3D geometries. In the paper, the recent researches on the 3D effects of stress concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 39 publications
0
9
0
2
Order By: Relevance
“…For the finite thickness plate, 0 ≤ T z ≤ ν, where ν is Poisson's ratio of the material. The third parameter is the equivalent thickness B eq of the point on the crack front line empirically defined by She et al [39]:…”
Section: Definitionmentioning
confidence: 99%
“…For the finite thickness plate, 0 ≤ T z ≤ ν, where ν is Poisson's ratio of the material. The third parameter is the equivalent thickness B eq of the point on the crack front line empirically defined by She et al [39]:…”
Section: Definitionmentioning
confidence: 99%
“…基 于这一点, 曲线裂纹上某一点 P 处的等效厚度可以由 其具有相同 T z 分布的穿透直裂纹板的厚度来确定, 如图 12 所示. 图 13-16 分别给出了穿透直裂纹 [36] (图 13)、 四分 之一椭圆角裂纹 [40] (图 14), 半椭圆表面裂纹 [41] (图 15) 以及内埋裂纹 [42] (图 16)的等效厚度研究结果, 其中 t 为椭圆形状比(t=a/c). 下面分别给出各种裂纹的裂纹 前沿线上某点的等效厚度 B eq .…”
Section: 各种典型裂纹的等效厚度unclassified
“…最初 的 B eq 被经验地定义为裂纹前沿线的切线与结构表面 的交点与切点的最短距离的两倍, 如图 10 所示. 后 来, 对于含有穿透直裂纹的平板, She 等人[36] 研究了 三维约束从板的中心面到表面的变化, 并基于约束 等效的原则, 提出了一种基于离面应力约束因子 T z 的等效厚度的定义, 如图 11 所示. 对于厚度为 B eq 的 穿透直裂纹(如图 11(b)), 中面上 T z 沿着 r 方向的分布 (z=0,     可以通过以下公式进行描述[36] :…”
unclassified
“…Stress field and stress concentration factor in 3D models of elliptic holes in flat rectangular bars were also studied numerically by Yang (2009), Zhao et al (2008, Snowberger (2008), Pedersen et al (2007) etc. Yang (2009) showed that the plane stress condition of 3D models is approximately achieved by the 2D ones when the plate thickness tends to zero.…”
Section: Introductionmentioning
confidence: 99%